Identification of a new prostate cancer susceptibility locus on chromosome 8q24. - Yeager, M; Chatterjee, N; Ciampa, J; Jacobs, K; Gonzalez-Bosquet, J; Hayes, R; Kraft, P; Wacholder, S; Orr, N; Berndt, S; Yu, K; Hutchinson, A; et al. (2009)
We report a genome-wide association study in 10,286 cases and 9,135 controls of European ancestry in the Cancer Genetic Markers of Susceptibility (CGEMS) initiative. We identify a new association with prostate cancer risk on chromosome 8q24 (rs620861, P = 1.3 x 10(-10), heterozygote OR = 1.17, 95% CI 1.10-1.24; homozygote OR = 1.33, 95% CI 1.21-1.45). This defines a new locus associated with prostate cancer susceptibility on 8q24.